2012
DOI: 10.1183/09031936.00228611
|View full text |Cite
|
Sign up to set email alerts
|

Airway impedance entropy and exacerbations in severe asthma

Abstract: Variability of peak flow measurements has been related to clinical outcomes in asthma. We hypothesised that the entropy, or information content, of airway impedance over short time scales may predict asthma exacerbation frequency.66 patients with severe asthma and 30 healthy control subjects underwent impulse oscillometry at baseline and following bronchodilator administration. On each occasion, airway impedance parameters were measured at 0.2-s intervals for 150 s, yielding a time series that was then subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…It is therefore possible that the associations that were observed in previous studies were at least partly related to the effect of proximal airway tone impacting upon the heterogeneity of distal airway calibre. Indeed, both we and others have previously found that pre‐bronchodilator physiological measurements correlate more strongly with asthma outcomes than post‐bronchodilator measurements.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is therefore possible that the associations that were observed in previous studies were at least partly related to the effect of proximal airway tone impacting upon the heterogeneity of distal airway calibre. Indeed, both we and others have previously found that pre‐bronchodilator physiological measurements correlate more strongly with asthma outcomes than post‐bronchodilator measurements.…”
Section: Discussionmentioning
confidence: 56%
“…The structural interpretation of IOS/FOT parameters has been the subject of much research, often based around computational models of lung impedance . The interpretations given in Table are based on our current knowledge, as previously reported . In particular, the resistance at 20 Hz (R20) is thought to represent the mean level of airway resistance throughout the airway tree, encompassing both large and small airways .…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported an association between bronchial hyper-responsiveness and community diversity and composition, secondary to an increased abundance of Proteobacteria (64). Bronchial hyper-responsiveness is accentuated during exacerbation and is an accurate predictor of future exacerbations (65). Alterations to the microbiome appear similar in both mild and severe disease and are specifically associated with features of the disease.…”
Section: The Microbiome Shapes Immunitymentioning
confidence: 99%
“…Forced oscillometry can assess both overall and peripheral airway mechanics by utilizing low frequencies that travel all the way to the small airways and, thus, reflect the whole airway tree and high frequencies that travel only proximally, mainly reflecting central airways. Studies have presented data on associations between forced oscillometry values thought to reflect distal airway pathology and clinical asthma outcomes in both children and adults . Further, an association between forced oscillometry values reflecting peripheral airways and markers of peripheral airway inflammation has been indicated in adult asthma …”
Section: Introductionmentioning
confidence: 99%